2011
DOI: 10.1073/pnas.1110566108
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells inhibit acute IFN-γ synthesis without blocking T-helper cell type 1 (Th1) differentiation via a compartmentalized requirement for IL-10

Abstract: CD4 + CD25 + Forkhead box P3 (Foxp3) + regulatory T cells (Tregs) control immune responses to self and foreign antigens in secondary lymphoid organs and at tissue sites of inflammation. Tregs can modify the function of many immune cells and have been proposed to block early proliferation, differentiation, and effector function. Acute ablation of Tregs has revealed rapid cytokine production immediately after Treg removal, suggesting that Tregs may regulate effector function acutely rather than regulating the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
76
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 41 publications
6
76
0
Order By: Relevance
“…For instance, these Treg-associated mediators are known to diminish the presence of inflammatory cytokines such as IFN-γ and IL-17 (32,33). Notably, Th type 1 (Th1) and Th17 cells, which are associated with high levels of IFN-γ and IL-17 expression, have been previously implicated to exacerbate periodontal disease symptoms (31)(32)(33)(34)(35). Consistent with the idea that recruited Tregs may regulate this process, our data (Figs.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…For instance, these Treg-associated mediators are known to diminish the presence of inflammatory cytokines such as IFN-γ and IL-17 (32,33). Notably, Th type 1 (Th1) and Th17 cells, which are associated with high levels of IFN-γ and IL-17 expression, have been previously implicated to exacerbate periodontal disease symptoms (31)(32)(33)(34)(35). Consistent with the idea that recruited Tregs may regulate this process, our data (Figs.…”
Section: Discussionsupporting
confidence: 78%
“…It is well known that these regulatory cytokines are secreted by Tregs, and are a mode by which Tregs exert a protective effect (28). For instance, these Treg-associated mediators are known to diminish the presence of inflammatory cytokines such as IFN-γ and IL-17 (32,33). Notably, Th type 1 (Th1) and Th17 cells, which are associated with high levels of IFN-γ and IL-17 expression, have been previously implicated to exacerbate periodontal disease symptoms (31)(32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with previous studies by Lal et al and Prinz et al [35,36]. However, the relationship between reduced Treg cells and enhanced Th17 cell responses is not clear, given that Treg cells are not so effective in the control of Th17 responses as in the suppression of Th1 responses [37,38]. Consistent with our current report, Fang et al [39] reported that the single TLR-1/2 agonist Pam3CSK4 exacerbated EAU with a suboptimal immunization protocol.…”
Section: Discussionsupporting
confidence: 83%
“…Thus, an important implication of our results is that such impaired IFN-g production would be restored to the normal level by a timely decrease in Treg frequency occurring at the late stage of EH, which is the key to successful resolution of an infection. Our Treg-depletion experiments showed that IFN-g responses were more sensitive to the action of Tregs than were TNF-a responses, which are in accordance with the recent data in mice showing that acute shutoff effector cytokine production by Tregs was selective for IFN-g but not TNF-a (28). If so, therapeutic inactivation of Tregs may provide a greater benefit for protective immunity to HSV in a setting of genetically impaired IFN-g responses.…”
Section: Hsv-specific Cd4supporting
confidence: 79%